Uso de microorganismos benéficos en el cultivo de uchuva (Physalis peruviana L.) - Wilches-Ortiz, Wilmar Alexander; Ramírez-Gómez, María Margaita; Serralde-Ordoñez, Diana Paola; Peñaranda-Rolón, Andrea María; Díaz-García, Andres (Revista Mexicana de Ciencias Agrícolas, 2025)
Cape gooseberry (Physalis Peruviana L.) is a tropical fruit of interest for export in Colombia; one of the leading causes of low productivity is associated with susceptibility to Fusarium oxysporum f.sp. physali (Foph), cause of vascular wilt. This study aimed to evaluate the use of Arbuscular Mycorrhizal Fungi (AMF) and Plant Growth Promoting Rhizobacteria (PGPR) individually and in mixture, as a strategy to grant crop tolerance to the disease. For this, a trial was established in the field (Granada, Cundinamarca, Colombia) with three cape gooseberry materials in which three treatments were evaluated; correspond to inoculation with beneficial microorganisms with AMF (Rhizoglomus irregulare and Acaulospora mellea) (T1), AMF + PGPR (Bacillus subtillis) (T2), and control without inoculation (T3). The fertilization of the treatments T1 and T2 was carried out at 50% and for treatment T3 at 100%. The severity of the disease, agronomic development variables, crop production and fruit quality were evaluated. The results showed a relationship between the application of AMF with the weight with and without cape of fruits, export fruits, and plant height. A relationship was also observed between the application of AMF+PGPR with yield, the number of fruits, and Brix degrees. Finally, in all materials, it was observed that without inoculation, the progress of vascular wilt was favored, and the number of fruits that did not meet export criteria was increased. Therefore, it can be concluded that inoculation in the nursery and application with beneficial microorganisms exerts an antagonistic effect on vascular wilt disease caused by Foph.
Keywords: Acaulospora mellea; Bacillus subtillis; Fusarium oxysporum f. sp. physali; Rhizoglomus irregulare